2004
DOI: 10.1667/rr3158
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Inhibits Radiation-Induced Apoptosis of HUVECs. I. The PI3K/AKT Pathway and Induction of Phosphorylation of BAD

Abstract: Radiation-induced endothelial cell apoptosis is involved in the development of many radiation injuries, including radiation-induced skin ulcers. The proangiogenic growth factors basic fibroblast growth factor (bFGF, NUDT6) and VEGF enhance endothelial cell survival. In the present study, we used primary cultured human umbilical vein endothelial cells (HUVECs) irradiated with (60)Co gamma rays to explore the effects of bFGF on radiation-induced apoptosis of HUVECs and its signaling pathways. We found that bFGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…Hesperidin and doxorubicin show decreasing of Bcl-2 level on HeLa. Hesperidin suppressed TPAstimulated NF-κB translocation into the nucleus through IκB inhibitory signaling pathways and also inhibited TPA-induced AP-1 activity by the inhibitory phosphorylation of p38 kinase and c-Jun N-terminal kinase (JNK) signaling pathways (Lee et al, 2010) and inhibition of PI3K path that eventually spur apoptosis through inhibition of inactivation of Bad (Gu et al, 2004). Increased apoptosis by the combination of hesperidin and doxorubicin via inhibition of NF-κB activation can also occur through inhibition of MAP kinase and PI3K path.…”
Section: Effect Hesperidin and Doxorubicin On Bcl-2 And Bax Expressiomentioning
confidence: 99%
“…Hesperidin and doxorubicin show decreasing of Bcl-2 level on HeLa. Hesperidin suppressed TPAstimulated NF-κB translocation into the nucleus through IκB inhibitory signaling pathways and also inhibited TPA-induced AP-1 activity by the inhibitory phosphorylation of p38 kinase and c-Jun N-terminal kinase (JNK) signaling pathways (Lee et al, 2010) and inhibition of PI3K path that eventually spur apoptosis through inhibition of inactivation of Bad (Gu et al, 2004). Increased apoptosis by the combination of hesperidin and doxorubicin via inhibition of NF-κB activation can also occur through inhibition of MAP kinase and PI3K path.…”
Section: Effect Hesperidin and Doxorubicin On Bcl-2 And Bax Expressiomentioning
confidence: 99%
“…Conventional radiation doses are believed not to activate the ceramide-dependent apoptosis pathway. Basic fibroblast growth factor (bFGF) has been shown to inhibit ceramide-dependent messaging for apoptosis [10,[15][16][17][18][19]. In comparison, epithelial and tumor cells are predominantly damaged through direct or indirect DNA damage, and undergo cell death or senescence only when they have accumulated adequate damage [9,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that activation of Akt pathway including other mitogenic and survival signaling are critical for the growth, survival and migration of endothelial cells (Kim et al, 1993;Qi et al, 1999;Carmeliet, 2002;Chen et al, 2004;Gingis-Velitski et al, 2004;Gu et al, 2004). Nuclear factor kappa B (NF-kB), a hetrodimeric transcription factor, is known to modulate the transcription of genes responsible for the growth and survival as well as inhibition of apoptosis (Baldwin, 1996;Baeuerle and Baltimore, 1996;Levkau et al, 1999;Malyankar et al, 2000;Yamamoto and Gaynor, 2001).…”
Section: Introductionmentioning
confidence: 99%